Social determinants of health : assessing theory, policy, and practice (New perspectives in South Asian history, 2010)
The World Health Organization's Commission on Social Determinants of Health released its Final Report in 2008. This is a landmark document that hopes to kick-start a major global movement for health equity a laudable goal, considering that serious health inequities continue to afflict most nations, including those with the most developed economies. However, many challenges await the Report's advocates, both within global and national contexts. Political and economic difficulties will need to be surmounted, allies in government and civil society will need to be mobilised and these alliances maintained, and a plethora of social conditions will require careful study and negotiation before policies are drawn up and implemented. Social Determinants of Health brings together a selection of proceedings drawn from a major conference held in London 2008 this was the first independent, inter-disciplinary and critical gathering to assess the Commission's Final Report, and the results were impressive. Apart from providing searching analyses of different sections of the document, the presentations also provided the basis for a fruitful engagement between academics and those involved in policy design and implementation. The papers presented in this volume provide us with numerous insights into the genesis, management and reception of global health projects, as they unfolded in international, national and local contexts. These analyses will be of interest to teachers, students, NGOs, national governments, global and international funding agencies, and others involved in health initiatives and advocacy.